Sodium-dependent glucose Co-transporter-2 inhibitor empagliflozin exerts neuroprotective effects in rotenone-induced parkinson's disease model in zebrafish; mechanism involving ketogenesis and autophagy - ALTURFAN, EBRU IŞIK (My University, 2023)
Sodium-dependent glucose co-transporter-2 (SGLT2) inhibitor empagliflozin (EMP), is the new class of oral hypoglycemic agent approved as a treatment for Type 2 diabetes. SGLT2 inhibitors may induce ketogenesis through inhibiting the renal reabsorption of glucose. In recent years, positive effects of ketogenic diets on neurodegenerative diseases such as Parkinson's disease (PD) have been reported by improving autophagy. We aimed to evaluate the effects of EMP treatment as a SGLT2 inhibitor that can mimic the effects of ketogenic diet, in rotenone induced PD model in zebrafish focusing on ketogenesis, autophagy, and molecular pathways related with PD progression including oxidative stress and inflammation. Adult zebrafish were exposed to rotenone and EMP for 30 days. Y-Maze task and locomotor analysis were performed. Neurotransmitter levels were determined by liquid chromatography tandem- mass spectrometry (LC-MS/MS). Lipid peroxidation (LPO), nitric oxide (No), alkaline phosphatase, superoxide dismutase, glutathione, glutathione S-transferase (GST), sialic acid, acetylcholinesterase, and the expressions of autophagy, ketogenesis and PD-related genes were determined. Immunohistochemical staining was performed for the microglial marker L-plastin (Lcp1) and tyrosine hydroxylase (Th). EMP treatment improved DOPAC/DA ratio, Y-Maze task, locomotor activity, expressions of Th and Lcp-1, autophagy and inflammation related (mTor, atg5, tnf, sirt1, il6, tnf); PD-related (lrrk2, park2, park7, pink1), and ketone metabolism-related genes (slc16a1b, pparag, and pparab), and oxidant-damage in brain in the rotenone group as evidenced by decreased LPO, No, and improved antioxidant molecules. Our results showed benefical effects of EMP as a SGLT2 inhibitor in neurotoxin-induced PD model in zebrafish. We believe our study, will shed light on the mechanism of the effects of SGLT2 inhibitors, ketogenesis and autopahgy in PD.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Klinik Tıp; Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); CLINICAL MEDICINE; NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Multidisipliner; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Multidisciplinary; Sodium-dependent glucose transporter; empagliflozin; Parkinson's disease; autophagy; ketogenesis